TOURISM INDUSTRY AND PERSONNEL TRAINING: MODERN REQUIREMENTS OF UZBEKISTAN - Rushana Rakhmanova (Western European Studies, 2024)
This article discusses the problems of economic and educational processes in the field of tourism in Uzbekistan, ways to overcome them and the consequences of staff shortages. The author notes the growing need for mature and highly qualified specialists in the field of tourism, noting that the current training practice in the country is largely based on theoretical knowledge, and the practical skills of students are poorly developed. In this sense, the emphasis is on the need to improve educational programs and training systems, strengthen cooperation with tourism enterprises, and create a system of mutually beneficial cooperation between business representatives and universities. At the same time, the importance of applying international standards in tourism is widely highlighted, through which it is possible to improve the quality of tourist services and positively affect the economic development of the country.
Keywords: tourism; personnel training; education